Investigating the conundrum related to treatment alternatives for Gestational Diabetes Mellitus (Research, Society and Development, 2024)
Objective: To elucidate the doubt in question of an antidiabetic drug that has good efficacy and safety in pregnant women and that can be used as a background for patients who, due to some bias, cannot or do not want to undergo their treatment with insulin; clarify the most commonly used medications to treat GDM, both by efficacy and by the patient's wishes. Also, bring information about the disease in question.  Methods: The main means of data collection is the research Google Scholar, Pubmed, Scielo, Brazilian Society of Diabetes Guideline and Febrasgo. The method of choice was evaluated based on the positive and negative points of both medications, efficacy and safety. Results and discussion: Insulin is associated with the need for high daily doses of insulin therapy, and the need for high daily doses of insulin therapy, difficulty in self-administration, stress resulting from its use, and weight gain Metformin has been shown to reduce preterm births and cesarean sections, decreased maternal obesity and with fewer results of macrosomia, jaundice and hypoglycemia. More women in the metformin group than in the insulin group said they would choose to receive their assigned treatment again. Conclusion: Metformin has been shown to be efficient in controlling blood glucose, safe for pregnant women and without evidence of teratogenicity. Insulin still remains the drug of choice because it is a molecule with a small placental passage and its Low immunogenic risk.